Menggugat Allah: Pendekatan Sosio-ideologis terhadap Gugatan Ayub dalam Ayub 24:1–12 - Albert Parsaoran Sihotang (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
The book of Job is one of the stories that excitingly describes the encounter of both the reality of life and the utopian faith’s tradition in the life of a pious and righteous person before God. The tension from the encounter between them is conveyed uniquely in the dialogue between Job, God, and his friends, using the form of confrontation and confirmation. Although the historicity of Job’s figure can be questioned, his characterizations that show a person’s religiosity represent the religiosity of the community. Job is present not only in the tension of confrontation and confirmation but also as a transformative solution between the fragile realities of life (vulnerability to suffering) and the utopian faith’s tradition that tends to hegemony the reality of life. Therefore, through a socio-ideological hermeneutical approach, this research tries to reread Job’s story specifically through chapters 24:1-12 which highlights Job’s claim. In this study, it appears that Job’s claim, which has been neglected due to the dominance of “one-sided” readings on the righteous and pious character of Job, has become a transformative solution as a realistic and authentic form of religiosity in the tension of encountering the realities of life and the traditions of faith.